K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

19 tháng 10 2017

Biến đổi VT=\(3\left(ab+bc+ca\right)-abc\left(a+b+c\right)=3\left(ab+bc+ca\right)-\frac{\left(ab+bc+ca\right)^2-a^2b^2-b^2c^2-c^2a^2}{2}\)

\(\le3t-\frac{t^2}{2}+\frac{3}{2}=\frac{12-\left(t-3\right)^2}{2}\le6\)(t=ab+bc+ca)

(a^2b^2+b^2c^2+c^2a^2 nhỏ hơn hoặc bằng 3)

17 tháng 10 2017

1a + 2a + 3a:5a 

= 3a + \(\frac{3}{5}\)a

= 3\(\frac{3}{5}\)a = \(\frac{18}{5}\)a

K nha

17 tháng 10 2017

a + 2a + 3a : 5a

= a ( 1 + 2 + 3 ) : 5a

= 6a : 5a = 6/5

= 1,2

Bài này lớp 3 còn làm được